Determinación de parámetros productivos en tres estirpes de pollos en la quinta experimental Punzara de la Universidad Nacional de Loja - Aguilar Agreda, Richard Javier (2015)
The present research work centers on a Poultry Program of Punzara Experimental Farm belonging to Universidad Nacional de Loja, whose objective is to know the productive parameters of the three types of chicken meat which are commercialized and consumed in Loja. Some variables were identified; food consumption, weight gain, FCR, high quality standards in poultry industries and the economy efficiency of the above mentioned topic. Three hundred chickens of different industries were selected, they were given different treatments, each group of one hundred animales with four repetitions taking twenty five chickens at a time. The balanced chicken feed that was given was totally commercial. During the food consumption the one that was used the most was T1 (Kiquirik) 6151,60 grams, the highest weight was for T3 (Cobb 500) with 2358 grams, the FCR cumulated was better with T3 (Cobb 500) with 2, 10. Likewise, the best performance to the canal was T3 (Cobb 500) which presented the highest efficiency with nearly 83, 55%. In relation to the poultry economy efficiency the T1 (Kiquirik) the profitability was 11% and the one with the lowest mortality rate was the T1 (Kiquirik) with 9%. The best race during this breeding intensive system was the T3 (Cobb 500). The other brands were inferior in relation to the aforementioned parameters, they can be exploded in semi-intensive conditions where their adaptation contributes to improve their quality. It is important to take into account that their palatability is quite good in contrast to a Broiler chicken. Keywords: low growth, camper chickens, brands chicken meat.